Meeting the Challenge of COVID-19 in DHQ Orthopaedic Department - Obaid ur Rahman , Nayyar Qayyum, Afzaal Aleem Khan, Mohammad Ammar Aslam, Zohaib Haider, Obaid ur Rahman , Nayyar Qayyum, Afzaal Aleem Khan, Mohammad Ammar Aslam, Zohaib Haider; Obaid ur Rahman ,Nayyar Qayyum ,Afzaal Aleem Khan ,Mohammad Ammar Aslam ,Zohaib Haider (Journal of Rawalpindi Medical College, 2020)
Introduction: The World Health Organization (WHO) declared Covid-19 as a pandemic on March 11, 2020. Not only that the COVID-19 pandemic has brought the world to a complete lockdown but also burdened healthcare systems across the world immensely. Objective: In this paper, we discuss the different strategies we adopted in the Orthopaedics Department of District Head Quarter [DHQ] hospital Rawalpindi, during this ongoing pandemic and share our experience of successfully but cautiously providing orthopedic services to patients in a public hospital. We compare our workload and output of May 2020 [pandemic phase] to May 2019 [standard/normal phase]. Methodology: The Hospital policy was changed after the COVID-19 pandemic. We increased public awareness and reduced load in the OPD using different strategies. We postponed all elective cases; focusing our logistics and resources only on the patients in urgent need of surgical management. A minimum number of doctors and OTAs were allocated on each list. Inwards, the patient stay was reduced. As a standard PCR test for COVID-19 was expensive, we devised our screening through history, examination, and routine investigations. Results: The average stay inwards was reduced from 6.4±4.6 days in May 2019 to 2.7±3.6 days in May 2020. The decrease in the stay was statistically significant (p=.0206) and was associated with a 24.4% increase in the number of total patient admissions in May 2020 (n=56) as compared to May 2019 (n=45). The number of surgeries performed month to month was very similar in normal and pandemic periods. Our OPD patient attendance dropped from 200-250 patients per day in 2019 to 60-70 during the ongoing pandemic phase. Conclusion: We believe that sharing experiences between health care actors allows us to develop an effective strategy to provide the very best care to our patients during the COVID-19 pandemic.